2013
DOI: 10.1080/01425692.2013.777211
|View full text |Cite
|
Sign up to set email alerts
|

Understanding critical race theory as a framework in higher educational research

Abstract: This paper reviews the existing literature to discuss how critical race theory has been applied as a theoretical framework to higher educational research in the United States and what its contributions are. To provide necessary context, I will discuss race and racism in the United States, the background of US higher education in relation to race, the emergence of critical race theory and its application in US higher education. Race and racism in the United StatesRace has been long studied by social scientists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…Sixteen percent of BAME students reported experiencing racism in the NUS research (NUS & Universities UK, 2019), whilst in the present study, 50% reported experiencing any kind of discrimination. These results eschew university's colour-blindness by adding to the concrete body of evidence that BAME students are disadvantaged within universities in the United Kingdom (Brown & Jones, 2013;Bunce et al, 2019;McDuff et al, 2018;NUS & Universities UK, 2019;NUS, 2012) and elsewhere (Savas, 2014;Sol orzano & Yosso, 2002). Given universities typically have established support systems already in place (including assessment and mental health support), widening the accessibility of these to all students, especially BAME students, can be an immediate and significant anti-racist gain.…”
Section: University Support and Discriminationmentioning
confidence: 88%
See 1 more Smart Citation
“…Sixteen percent of BAME students reported experiencing racism in the NUS research (NUS & Universities UK, 2019), whilst in the present study, 50% reported experiencing any kind of discrimination. These results eschew university's colour-blindness by adding to the concrete body of evidence that BAME students are disadvantaged within universities in the United Kingdom (Brown & Jones, 2013;Bunce et al, 2019;McDuff et al, 2018;NUS & Universities UK, 2019;NUS, 2012) and elsewhere (Savas, 2014;Sol orzano & Yosso, 2002). Given universities typically have established support systems already in place (including assessment and mental health support), widening the accessibility of these to all students, especially BAME students, can be an immediate and significant anti-racist gain.…”
Section: University Support and Discriminationmentioning
confidence: 88%
“…mitigation and who cannot; Salter & Adams, 2013). This unique knowledge can valuably inform anti-racism (Aguirre, 2000;Savas, 2014;Sol orzano & Yosso, 2002;Yosso, 2013).…”
mentioning
confidence: 97%
“…CRT frameworks have been used to analyze the experiences and outcomes of minority ethnic academics particular to the complex contexts of higher education in the USA (Hiraldo 2010;Savas 2014). Scholars utilize a CRT analysis to highlight the experiences of minority ethnic academics in PWIs (Delagdo et al 2002;Espino 2012;Griffin et al 2014); critique institution diversity policies (Aguirre 2000;Donahoo 2008); analyze intersections of race, class, and gender among faculty (Sulé 2014;Solorzano 1998) and document the racial climate in universities (Harper 2012;Orelus 2013;Pittman 2012).…”
Section: Crt Analysis Of Ime Experiences In Pwis In the Usamentioning
confidence: 99%
“…Leonardo asserts that, "whiteness can be demarcated and fenced off as a territory of white people which keeps Others out (2002,38). The articulation of White boundaries and territorial racial stratifications serve as barriers that prevents IME academics from becoming fully engaged scholars in their departments and universities (Hiraldo 2010;Savas 2014). Moreover, the presence of non-White faculty challenged the normativity of Whiteness, and placed intellectual spaces, as epi-centers of White property, in jeopardy of being corrupted, and in need of protection.…”
Section: Navigating Whiteness and White Privilegementioning
confidence: 99%
“…Thus, the intersecting theoretical concepts through which the study was designed and analyzed include critical race theory; sociological notions of capitals, understandings of structural and symbolic violence; and theories of agency and emancipation. Critical race theory was employed to highlight how the intersection of multiple social identities impact student experiences (Crenshaw, Gotanda, Peller, & Thomas, 1995; Mclaughlin & Whatman, 2011; Savas, 2014; Solorzano & Yosso, 2000, 2002). An analysis of different forms of capitals allowed us to discern the many forms of capital required for success, linking economic, cultural, and social capital structures to inequalities, while emphasizing the individual in larger systemic influences (Bourdieu, 1997; Bourdieu & Wacquant, 1992; Farmer, 1996; Putnam, 2000; Swartz, Harding, & De Lannoy, 2012).…”
Section: Introductionmentioning
confidence: 99%